2011
DOI: 10.4276/030802211x13074383957823
|View full text |Cite
|
Sign up to set email alerts
|

Wii Health: A Preliminary Study of the Health and Wellness Benefits of Wii Fit on University Students

Abstract: The aim of this preliminary study was to determine the effectiveness of the Nintendo Wii Fit as an occupation to promote weight loss in undergraduate students. Participants: Five first-year female students living on campus at a northeastern university in the United States were recruited to participate in this study. Method: An A-B single subject design was created where participants were separated into three groups: a typical activity group and two Wii conditions (Wii Fit individually and Wii Fit with another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 20 publications
0
51
0
Order By: Relevance
“…Bacon, Farnworth and Boyd (2012) introduced the Wii Fit to patients in a forensic mental health setting using group sessions as well as access in between these sessions. Jacobs et al (2011) provided the Wii Fit to university students for use in four weekly sessions. Both studies found some improvement in attitude to and engagement in physical activity.…”
Section: Quantitative Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacon, Farnworth and Boyd (2012) introduced the Wii Fit to patients in a forensic mental health setting using group sessions as well as access in between these sessions. Jacobs et al (2011) provided the Wii Fit to university students for use in four weekly sessions. Both studies found some improvement in attitude to and engagement in physical activity.…”
Section: Quantitative Studiesmentioning
confidence: 99%
“…An occupational therapy role was advocated at a population, or community level to help increase the physical activity level of children and young people (Ketteridge & Boshoff, 2008;McMullan et al, 2012;Pont et al, 2011;Poulsen & Ziviani, 2004;Stanley et al, 2007;Ziviani et al, 2006Ziviani et al, , 2010. Interventions were also described which targeted the needs of groups identified at increased risk of obesity, such as children from low socio-economic and urban areas who may have decreased access to opportuni- ties for participation (Cahill & Suarez-Balcazar, 2009;Knis-Matthews et al, 2005;Ziviani et al, 2008), university undergraduates who are identified as being prone to gaining weight (Jacobs et al, 2011) and people living with severe mental illness, who are at risk of obesity as a result of a range of factors, including decreased physical activity, medication side effects and reduced access (Lloyd et al, 2003;Northey & Barnett, 2012) and those held in forensic settings, for whom access is an issue (Bacon et al, 2012).…”
Section: Focus Of Occupational Therapy Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The games can, according to several studies, provide a tool to increase physical activity levels to improve the fitness and health of young people (Fogel et al, 2010;Graves et al, 2010;Jacobs et al, 2011;Sell et al, 2010). In this endeavor, increased heart rate, energy expenditure, and weight control seem to stand out as important educational intervention objectives (Graves et al, 2007Jacobs et al, 2011, Quinn, 2011, and the targets of the intervention are primarily children with sedentary lifestyles (Cunningham et al, 2010;Hansen & Sanders, 2010). For this to be possible, the activities and, in this case, the exergames have to be fun and enjoyable and thus motivate and sometimes trick the children into exercising (Cunningham et al, 2010;Graves et al, 2010;Staiano & Calvert, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…These studies have shown an increase in heart rate and an increase in oxygen consumption. This energy consumption is statistically significantly higher compared to non-active video games and sedentary activities, despite the variability of the types of active video games, as well as the time spent playing them [5,7,19,[22][23][24][25][26]33].Regarding the effect of active video games on body mass index (BMI), various primary studies [21,31,[33][34][35][36][37][38][39][40][41] have analyzed their effect using BMI as one of their dependent variables. However, no meta-analyses have been found focused on the BMI variable in children and adolescents.Studies regarding the impact of active video games on BMI suggest that active video games can be a very good opportunity for reducing BMI, and with it, the prevalence of overweight and obesity, especially in children and adolescents.…”
mentioning
confidence: 99%